Automated, semi‐automated, and manual analyses of anti‐cardiolipin and anti‐β2‐glycoprotein I antibodies in women with a history of miscarriage. Issue 2 (4th October 2012) - Gutensohn, K.; Vossen, D.; Strate, A.; Kersten, J. F.; Hofbauer, M.; Krieger, T.
Summary Introduction Anti‐cardiolipin and β2‐glycoprotein I antibodies represent important diagnostic parameters in routine hematology. In this study, five different automated, semi‐automated, and manual immunoassays detecting IgG/IgM anti‐cardiolipin and anti‐β2‐glycoprotein I antibodies were tested. Methods A total of 162 samples from women with a history of miscarriage were recruited from 110 different G&O outpatient centers in Germany. Results For both anti‐cardiolipin and anti‐β2‐glycoprotein I antibodies, considerable differences in the percentage of positive results were seen between all five methods, and itemization of all positive test results revealed a poor accordance. These findings were confirmed by Cohen's kappa coefficients. Conclusion Our study revealed a moderate to poor accordance between five different test systems for anti‐cardiolipin and anti‐β2‐glycoprotein I antibodies. Such deviations may result in clinical misinterpretation of data and may lead to wrong therapeutic consequences. Therefore, further standardization of all tests for anti‐phospholipid antibodies should be achieved.